Investigating the Antidepressant-like Effects of some Benzimidazole-piperidine Derivatives by In-Vivo Experimental Methods - Turan, Nazlı; Özkay, Ümide D.; Can, Nafiz Öncü; Can, Özgür Devrim (Letters in Drug Design & Discovery, 2019)
Background: Benzimidazole and piperidine rings are important pharmacophore groups for drug design studies. Objective: In this study, we aimed to investigate the antidepressant-like activity of some 2-(4- substituted-phenyl)-1-[2-(piperidin-1-yl)ethyl]-1H-benzimidazole derivatives. Methods: Tail-suspension Test (TST) and Modified Forced Swimming Tests (MFST) were used to assess antidepressant-like activities of the test compounds. Moreover, locomotor activity performances of the animals were evaluated by an activity cage device. Results: In the TST and MFST, compounds 2c-2h (10 mg/kg) and the reference drug fluoxetine (20 mg/kg) significantly reduced the immobility time of mice indicating the antidepressant-like activities of these compounds. Further, in MFST, the same compounds induced significant enhancement in the duration of active swimming behaviors without affecting the climbing performance of the animals. This prolongation in the swimming time, similar to fluoxetine, pointed out that antidepressant- like activity of the compounds 2c-2h might be related to the serotonergic rather than noradrenergic mechanisms. Besides, results of the activity cage tests demonstrated that none of the tested compounds caused an alteration in the locomotor activities of mice, signifying that antidepressantlike effects presented in this study were specific. Conclusion: In conclusion, results of this present study supported the previous papers reporting the therapeutic potential of compounds carrying benzimidazole and/or piperidine rings in their structure and emphasized, once again, the importance of these pharmacophore groups in drug design studies.
Keywords: benzimidazole